2013
DOI: 10.1186/1297-9686-45-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of using genealogy-based haplotypes for genomic prediction

Abstract: BackgroundGenomic prediction uses two sources of information: linkage disequilibrium between markers and quantitative trait loci, and additive genetic relationships between individuals. One way to increase the accuracy of genomic prediction is to capture more linkage disequilibrium by regression on haplotypes instead of regression on individual markers. The aim of this study was to investigate the accuracy of genomic prediction using haplotypes based on local genealogy information.MethodsA total of 4429 Danish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…By this method, equal size can be determined through physical length in base pairs (Ferdosi et al, 2016;Hess et al, 2017), the length in centimorgans (Sun et al, 2015), or the number of SNPs ). In addition, methods to define haplotypes such as combining information about identity by descent (IBD) with clusters of adjacent SNPs (Calus et al, 2008;Calus et al, 2009), and using predicted genealogy (Edriss et al, 2013) were studied. Also, setting minimum pairwise LD cutoffs to grouped SNPs into haplotypes was considered (Cuyabano et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…By this method, equal size can be determined through physical length in base pairs (Ferdosi et al, 2016;Hess et al, 2017), the length in centimorgans (Sun et al, 2015), or the number of SNPs ). In addition, methods to define haplotypes such as combining information about identity by descent (IBD) with clusters of adjacent SNPs (Calus et al, 2008;Calus et al, 2009), and using predicted genealogy (Edriss et al, 2013) were studied. Also, setting minimum pairwise LD cutoffs to grouped SNPs into haplotypes was considered (Cuyabano et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Simulation studies that compared genomic selection using CL haplotypes vs. genomic selection using SNPs showed that selection accuracies of CL haplotypes were lower than those based on SNP markers . However, recent empirical comparisons using higher marker densities revealed that CL haplotype-based genomic selection gave slightly higher genomic prediction accuracy than did individual SNPs (Cuyabano et al, 2014(Cuyabano et al, , 2015Edriss et al, 2013). One of the problems associated with CL haplotypes is the possibility that the predicted haplotype data might be compromised by errors in map construction.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in many instances genomic selection [1] assumes a large number of unlinked loci. As discussed in previous work it has implications in genomic evaluations that are systematically ignored [2,3,23]: a) progeny from the same parent share large haplotypes (not just single SNP) as shown with ROIs in this paper, and b) single heterozygous SNPs for both sire and half-sib progeny are non-informative, and consequently information is reduced or lost in genomic evaluations. Other advantages and potential applications of the proposed method are: 1) requires only currently available genotypic information on progeny as required for genomic selection when using juveniles for shortening generation intervals, 2) can be applied to any farm animal with large families even if only one parent is common to a group of progeny, 3) facilitates haplotyping the entire breeding population for new investigations such as signatures of selection or high order linkage disequilibrium, 4) can be used to estimate molecular relatedness more precisely by using haplotypes of given length rather than the sum of single SNPs (large fragments are likely identical by descent), and 5) can help to tracing up allele and haplotypes through generations which may facilitate the detection of genes involved in diseases or production.…”
Section: Discussionmentioning
confidence: 88%
“…Haplotype phasing consists of arranging the order of allelic variants in a chromosomal segment within each of the two homologous chromosomes of diploid species. Phasing knowledge can be applied to trace SNP inheritance and to account for regions that are identical by descent in genomic evaluations aimed at the genetic improvement of agricultural species [2,3]. Haplotype phasing can be assessed in the laboratory or computationally [4].…”
Section: Introductionmentioning
confidence: 99%